Tumour-promoting activity of altered WWPI expression in breast cancer and its utility as a prognostic indicator - Huu, N.; Ryder, W.; Zeps, Nikolajs; Flasza, M.; Chiu, M.; Hanby, A.; Poulsom, R.; Clarke, R.; Baron, M. (John Wiley & Sons Ltd, 2008)
WWP1 is a ubiquitin ligase, associated with the post-translational regulation of several tumour-promoting and tumour suppressor proteins. Here we show that WWP1 expression is up-regulated in a subset of breast tumour cell lines and primary breast tumours. We overexpressed WWP1 in MCF10A breast epithelial cells and demonstrated increased cell growth and anchorage- independent colony formation. RNAi knockdown of WWP1 expression in T47D and MCF7 breast tumour cell lines reduced anchorage-independent colony formation. We used WWP1 protein expression levels, in combination with its subcellular localization, to classify breast tumours into four categories. Surprisingly, a category with low/absent WWP1 expression displayed a consistently worse prognosis compared with WWPl-expressing tumours. Importantly, the association with disease-free survival was independent of the status of other commonly used prognostic indicators. Thus, WWP1 is a prognostic marker and may be a potential therapeutic target for a subset of breast tumours. Copyright © 2008 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.